Le buste de Tanit à Ibiza : un objet, une égérie, une identité - Élodie Guillon (Pallas, 2022)
The article studies the reception of a terracotta bust from the Punic period. Discovered in Ibiza, it has become a very famous emblem of the island. Starting with its discovery in 1913, the article describes the reception it has received, both in the scholarly sphere and in popular culture. It focuses in particular on the hippie period and on the industrialisation of tourism (since 1970s), which constitute two important moments in the reception of the bust. It also attempts to identify the mechanisms and processes that have led to its current status as a symbol of the island.